Work locus of control and sense of coherence as antecedents of job insecurity - J. Pienaar; H. De Witte (South African Journal of Business Management, 2016)
Previous research has highlighted various antecedents of job insecurity, both in cross-sectional research and in a recent meta-analysis. A review of this literature indicates that work locus of control actually is the only personality antecedent that has received considerable attention, while sense of coherence may also be an important factor to consider. Data on biographical variables, cognitive and affective job insecurity, work locus of control and sense of coherence were gathered from employees across 3 organisations (N=718), presenting two different sectors (chemical industry and financial services), by means of anonymous surveys. Data were analysed by means of correlations and regression analyses. Results indicate that both work locus of control and sense of coherence play a role in predicting job insecurity, even after controlling for biographical variables. Considering their individual contributions, it is suggested here that sense of coherence may be even more important than work locus of control as a personality antecedent of job insecurity.
Keywords: 650